Implementasi Kebijakan Pengentasan Kemiskinan di Kota Tanjungpinang melalui Program Bantuan Pangan Non Tunai (BPNT) Sebagai Upaya Mencapai Sustainable Development Goals (SDGs) (International Forum of Researchers and Lecturers, 2023)
Poverty is one of the major issues currently being faced by the Indonesian nation. The problem of poverty will never end if traced from the root of the problem. Poverty is not only an interesting issue to be discussed at the national level, but at the regional level itself, the poverty of this community seems to spread throughout the country, for example in Tanjungpinang City, where the poverty rate is high, even though Tanjungpinang City is the provincial capital. Various efforts and efforts have been made by related parties to reduce the poverty rate, but what is happening in the field is that the poverty rate is actually increasing. Starting from BLT assistance, PKH to BPNT, the local government has launched it in collaboration with related agencies, namely the Social Service. In this study, the researchers wanted to examine one of the aids, namely Non-Cash Food Assistance (BPNT), which is routinely carried out from 2018-present. Researchers want to know more about how this assistance is implemented, starting from the weaknesses to the advantages that arise from this assistance and what the consequences are for the poverty rate. Talking about the poverty rate cannot be separated from sustainable development or often referred to as the SDGs, where the first point of the SDGs is No Poverty (Without Poverty) whose target must be achieved by 2030. This study used a qualitative descriptive method, with 7 (seven) informants. In this study the techniques used were interviews and documentation. The theory used in this study uses the theory of Van Metter and Van Horn. The results of the study found that the implementation of the poverty alleviation policy through BPNT was quite good, but it is undeniable that there are still deficiencies that must be addressed, especially in determining the beneficiaries who receive this assistance, which often occurs miscommunication or mis-data between events that actually occur in the field. data received by related parties. Not only that, in the last few months the distribution has been changed from a system of buying food to cash which is disbursed directly through an ATM, of course this is a decision that must be reviewed again from the original purpose of this policy.